Current Epidemiology of Revision Total Hip Arthroplasty in the United States: National Inpatient Sample 2009 to 2013 - Gwam, Chukwuweike U.; Mistry, Jaydev B.; Mohamed, Nequesha S.; Thomas, Melbin; Bigart, Kevin C.; Mont, Michael A.; Delanois, Ronald E. (The Journal of arthroplasty, 2017)
Despite the excellent outcomes associated with primary total hip arthroplasty (THA), implant failure and revision continues to burden the healthcare system. THA failure has evolved and displays variability throughout the literature. In order to understand how THAs are failing and how to reduce this burden, it is essential to assess modes of implant failure on a large scale. Thus, we report: (1) etiologies for revision THA; (2) frequencies of revision THA procedures; (3) patient demographics, payor type, and US Census region of revision THA patients; and (4) the length of stay and total costs based on the type of revision THA procedure. We queried the National Inpatient Sample database for all revision THA procedures performed between January 1, 2009 and December 31, 2013. This yielded 258,461 revision THAs. Patients specific demographics were identified in order to determine the prevalence of revision procedure performed. Dislocation was the main indication for revision THA (17.3%), followed by mechanical loosening (16.8%). All-component revision was the most common procedure performed (41.8%). Patients were most commonly white (77.4%), aged 75 years and older (31.6%), and resided in the South US Census region (37.0%). The average length of stay for all procedures was 5.29 days. The mean total charge for revision THA procedures was $77,851.24. Dislocation and mechanical loosening is the predominant indication for revision THA in the United States. With the frequency of revision THAs projected to double in the next decade, orthopedists must take steps to mitigate this potentially devastating complication.